DETERMINAN KESIAPSIAGAAN KARYAWAN RUMAH SAKIT MENGHADAPI BAHAYA KEBAKARAN DI KOTA PEKANBARU - Endang Purnawati Rahayu; Indra Suandy; Yusri (Journal of Hospital Administration and Management (JHAM), 2026)
One of the fire risks that occur in buildings is hospitals. Hospitals have a high fire risk rating compared to other places. This is due to the activities carried out in hospitals, in addition, hospitals also use chemicals that pose a fire risk. The purpose of this study was to determine the determinants of hospital employee preparedness in facing fire hazards. The type of research used in this study is analytical-quantitative research. Sampling used random sampling of 150 employees with variable measurements (gender, length of service, education, knowledge, attitudes, fire experience and fire emergency response training). Data collection was carried out from primary and secondary data. Data analysis in this study was carried out using univariate and bivariate analysis with the chi-square test and multivariate analysis with the logistic regression test. The results obtained in this study were three variables that were significantly related to hospital employee preparedness in facing fire hazards in Pekanbaru City: knowledge, attitudes, and training. Therefore, the suggestion for hospitals is to routinely conduct emergency response training once a year, and conduct fire awareness campaigns at least once every six months to increase employee knowledge and preparedness in facing fire hazards in hospitals.